Literature Review: Heart Rate Variability as a Biomonitoring of Occupational Stress - Annes Waren; Muhammad Ilyas (Universitas Airlangga, 2021)
Introduction: Occupational stress is a modern epidemic. In terms of stress assessment, tools such as questionnaires are believed to be more subjective, especially in the assessment of stress in the workplace, while of course an objective assessment of stress also needs to be carried out. Objective examination for occupationalsstress will be very useful in the occupationalhhealth settings, which can early detect stress at work and prevent the long term effects. Therefore, this literature review aims to investigate the role of HRV in determining occupational stress. Methods: The searching methods used were PubMed and Google Scholar to find related journals about occupational stress and HRV, published in English. The articlessthatmmet the inclusion criteria were analysed basedoonothesstudy design, study population, occupationalsstressaand HRV assessment based on the Centre of Evidence-based Medicine, the University of Oxford for therapy study. Moreover, sample size varied from 8 to 1788. Results: It was found that there are three studies that fit the criteria, which are one systematic review study, one longitudinal study, and one cross-sectional study. The main finding from those articles was that occupational or job stress is found to be associated with lowered HRV value. Conclusion: HRV can be recommended for practicing occupational physicians and company doctors to identify the core areas of work- related stress.Keywords: biomonitoring, heart rate variability, coccupational stress